Judicial review : process, powers, and problems : essays in honour of Upendra Baxi / edited by Salman Khurshid, Sidharth Luthra, Lokendra Malik, Shruti Bedi. - Khurshid, Salman; Bedi, Shruti; Malik, Lokendra; Luthra, Sidharth (Cambridge University Press, 2020)
In India, judicial review is not a static phenomenon. It has ensured that the Constitution is the supreme law of the land, and in situations when a law impinges on the rights and the liberties of citizens, it can be pruned or made void. This is a collection of scholarly essays demonstrating the different facets of judicial review based on the vast area of comparative constitutional law. Importantly, it honours the body of work of Upendra Baxi, legal scholar and author, whose contributions have shaped our understanding of legal jurisprudence and expanded the scope of social transformation in India. This volume recognizes his role as an Indian jurist. Various constitutional law experts come together to reflect on his expositions on the role of the apex court, judicial activism, accountability of judiciary, laws on surrogacy and adultery and so on.